Reclaiming the F word : feminism today - Redfern, Catherine (Zed Books Ltd., 2013)
Feminism is so last century. Surely in today's world the idea is irrelevant and unfashionable? Wrong. Since the turn of the millennium a revitalised feminist movement has emerged to challenge these assumptions. Reclaiming the F Word is a generation-defining book that reveals the what, why and how of today's feminism, from cosmetic surgery to celebrity culture, from sex to singleness and now, in this new edition, the gendered effects of possibly the worst economic crisis ever.